The Evaluation of Investment Cooperation of Ukraine with EU Countries - Bulakh, T. M.; Ivashchenko, O. A.; Lytvyn, O. Ye. (Statistics of Ukraine, 2018)
The article investigates and evaluates the investment cooperation of Ukraine with the EU. The volume, structure and dynamics of investment flows between Ukraine and the European Union are analyzed. The main problems of cooperation between Ukraine and the EU are formed, in particular: the volume of foreign direct investment (FDI) in Ukraine from the EU is directed mainly to those sectors of the economy where it is possible quickly to make a profit (for example, in financial activities), while investment in priority sectors of the economy of Ukraine, aimed at a long-term growth, is insufficient. In addition, during the analysis of the investment market of Ukraine problematic aspects were found, such as: the existence of a tendency to invest in offshore zones, a low differentiation of foreign investors for donor countries and a sharp imbalance in the structure of FDI in the economy of Ukraine. The political instability, unpredictability of a state power, lack of independent judiciary (abuse of courts), corporate raiding, prosecution by tax authorities, shortcomings in the implementation of laws, delays and lack of transparency in VAT refund, corruption and the low level of property rights’ protection demonstrate the inability to build long-term plans with EU member states. Measures are proposed to improve investment cooperation between Ukraine and the EU in the context of deepening European integration processes, as follow: 1) bringing the strategy of attracting foreign investment in accordance with the needs of the country; 2) providing European investors with the necessary system support (for example, in business registration, attracting personnel); 3) creating the necessary conditions for the further implementation of the liberalization of the legal framework for the free movement of FDI in accordance with EU rules; 4) close cooperation with FDI donor countries; 5) providing conditions for improvement of technical and technological conditions of domestic enterprises; 6) production intensification on an innovative basis, etc.